Pengaruh Penerapan Adopsi Model Citizen’s Charter Terhadap Profesionalisme Kerja Aparat dan Kualitas Pelayanan Publik - Ismatul Mardiyah; M. Daimul Abror (Program Pascasarjana Universitas Negeri Makassar, 2017)
This study aims to analyze the influence of Citizen's Charter on the professionalism of the Workers Apparatus and the Quality of Public Service in Purwosari Sub-District, Pasuruan Regency. The research method used is quantitative with the entire population of Purwosari Subdistrict Apparatus which amounted to 22 respondents. While the data analysis used is simple linear regression analysis using SPSS program. The result of the research shows that calculation value for the influence of adoption of citizen's charter model to work professionalism is obtained t value> t table (4.583> 1.72) with significance value = 0.000 <0.05, so Ho is rejected. So it can be seen that adoption adoption model citizen's charter has a significant influence on professionalism of work, so that each indicator obtained positive results. The indicators to measure the professionalism of work which includes the value of efficiency is Demand or demand independence. As for the value of effectiveness consists of Dedication, Social Obligations, professional Regulation alone, and Affiliate professional community. While the result of calculation of influence adoption adoption model citizen's charter to public service quality also get t value bigger than t table that is equal to 6.000 with value signifikansi = 0.000 <0.05, so Ho rejected. So the adoption of citizen's charter model in Purwosari sub-district also significantly influences the quality of public service, so that every service quality indicator gets positive result. The indicators to measure the quality of services that include the value of efficiency is the speed and ease. As for the value of effectiveness consists of accuracy and fairness.